Private real estate investment : data analysis and decision making - Brown, Roger J. (Amsterdam ; Boston : Elsevier Academic Press, 2005)
This book is an essential partner in real estate research. Offering tools to enhance decision-making for consumers and researchers in market economies of any country interested in land use and real estate investment, the book will improve real estate market efficiency. With property the world's biggest asset class, timely data on housing prices just got easier to find and use.
Why location matters: the bid rent surface and theory of rent determination -- Land use regulation -- "Rules of thumb": threshold performance measures for real estate investment -- Fundamental real estate analysis -- Chance: risk in general -- Uncertainty: risk in real estate -- Tax deferred exchange -- Management problem -- Lender's dilemma -- Private lender -- Creative financing.
Includes bibliographical references and index.
aia 30/04/13
Loans
Keywords: Real estate investment -- Decision making; Real estate investment -- Planning